Iodine Supplementation: Usage “with a Grain of Salt” - Alessandro Prete; Rosa Maria Paragliola; Salvatore Maria Corsello (International Journal of Endocrinology)
Iodine supplementation through salt iodization is a worldwide, effective strategy for preventing iodine deficiency-related problems. Its safety and efficacy profile has been extensively investigated, and benefits far outweigh the potential iodine-induced risks. Moreover, iodine supplementation during pregnancy in order to avoid brain damage in the newborn is considered a mainstay of preventive medicine. Exposure to high amounts of iodine is actually well tolerated in most cases and can be unrecognized. Nevertheless, at-risk individuals may develop thyroid dysfunction even when they are exposed to increases in iodine intake universally considered as safe. Iodine-induced thyroid disorders include thyroid autoimmunity, thyrotoxicosis, iodine-induced goiter, and hypothyroidism. Moreover, a relationship between iodine intake and histotype distribution of differentiated thyroid cancer has been observed, with a progressive shift from follicular to papillary thyroid cancer. To date, evaluating iodine status in a clinical setting has limitations, and assessing the actual risk for each individual can be challenging, since it is influenced by personal history, genetics, and environmental factors. In conclusion, iodine supplementation programs need to be continued and strengthened, but iodine should be used “with a grain of salt,” because a growing number of susceptible individuals will be exposed to the risk of developing iodine-induced thyroid disorders.